Nivolumab induced inflammation of seborrheic keratoses: a novel cutaneous manifestation in a metastatic melanoma patient. Issue 5 (October 2018) - Rambhia, Pooja H.; Honda, Kord; Arbesman, Joshua
Abstract : Immune checkpoint inhibitors targeting the programmed cell death (PD)-1 receptor have dramatically changed the landscape of metastatic melanoma treatment. Nevertheless, these immuno-modulatory agents have associated side effects, including dermatologic manifestations. To this end, we report a patient with metastatic melanoma that was treated with a PD-1 inhibitor, and subsequently developed inflammation of existing seborrheic keratosis lesions and new verrucous keratoses, a cutaneous side effect that has not been previously reported to our knowledge. The etiology of seborrheic and verrucous keratoses is not well understood, although their physical and histopathologic similarities to chronic viral-derived lesions, such as human papilloma virus, suggest a potential viral association. Chronic viral infections are known to result in T-cell tolerance because of persistent antigen stimulation. PD-1 inhibition is able to reinvigorate exhausted T cells, which are accordingly able to decrease viral load. Thus, the inflammatory reaction, seen in our patient, may be the result of PD-1 inhibition reactivating virally driven T lymphocytes.